Linking Recruitment and Interpersonal Communication on Employee Performance through Work Motivation - Andi Kusumawardani; Syamsu Alam; Nurdjanah Hamid (Hasanuddin Journal of Business Strategy, 2021)
This study aims to analyze the influence of recruitment and interpersonal communication on employee performance using work motivation as a moderating variable at Energy Equity Epic Pty Sengkang, in Wajo Regency. Of 105 employees In the company, the study distributed questionnaires to 81 permanent employees that have been working for more than three years in the company. To analyze the collected data, the study applied quantitative research using Moderated Regression Analysis (MRA) with the help of SmartPLS software. On the basis of the study, The results showed that interpersonal communication significantly affects employee performance with a positive sign. Interestingly, the relationship between recruitment and employee performance shows a positive sign, but insignificant. With regard to moderating a variable, the study found that work motivation cannot mediate both relationships, recruitment, and interpersonal communication, to employee performance.